Use of High-Pass and Low-Pass Electrocardiographic Filters in an International Cardiological Community and Possible Clinical Effects - Parola, Franco (2017)
Background: High-pass and low-pass fi lters applied to 12-lead Electrocardiograms (ECG) are fundamental to avoid artifacts, but an inappropriate use may lead to misdiagnosis. Our goal is to evaluate cutoff points for these fi lters used as routine by cardiology professionals from different countries, and to determine to what extent they adjust to the established guidelines. Methods: We designed a descriptive study where 12-lead ECGs were included, both from adults and teenagers, distributed between August 2016 and February 2017 within the Ibero-American Forum on Arrhythmias on the Internet (FIAI) through the instant messaging apps WhatsApp and Telegram. Results: 48% of ECGs had at least one of the two fi lter cutoff points printed. The bandwidth recommended by different scientifi c societies (≤ 0.05 Hz and ≥ 150 Hz) was present in 2%. The most frequent low frequency cutoff value was 0.5 Hz (47%) and the high frequency one was between 25 Hz and 40 Hz (74%). As to the last consensus guidelines, we registered that 32% of ECGs met the low frequency cutoff point and just 5% the high frequency cutoff point. Conclusions: There is a high ratio of tracings lacking printed information on the fi lter used, and those that do have it, use inappropriate cutoff points in a high percentage, which may have significant diagnostic consequences.